Rezistencia mikroskopických húb voci vybraným antimykotikám - Kunová, Z (Epidemiologie, mikrobiologie, imunologie, 2002)
The author attended to enquiries of developing resistance of microscopic fungi (yeasts, micromycetes) to antimycotics used in therapy and their mechanisms of action.
Keywords: antifungální látky; Fungi; houby; Antifungal Agents; Drug Resistance, Fungal; fungální léková rezistence